An empirical investigation of the interplay between microcredit, institutional context, and entrepreneurial capabilities. Issue 3 (2nd July 2016) - Kimmitt, Jonathan; Scarlata, Mariarosa; Dimov, Dimo
Abstract: Understanding under which conditions microcredit is used by new, growing ventures is becoming increasingly pertinent to scholars. This paper investigates the interplay of the use of microcredit with entrepreneurial capabilities and the moderating role of institutional development in sub-Saharan Africa. Our findings show that higher constraints to entrepreneurial capabilities are associated with higher use of microcredit. In addition, we find that new, growing ventures use microcredit more where either economic or political institutions are less developed. Our findings suggest the importance of the existence of some type of institutional strength that must be in place to form the basis for microcredit activity. This allows for speculation as to whether microcredit works as the literature currently assumes.